1970
DOI: 10.3329/jom.v10i2.2821
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Diabetic Complications in a Diabetic Population

Abstract: This cross-sectional, questionnaire based descriptive study was carried out to evaluate the individual knowledge of diabetic complications in the diabetic patients and also to find the association of knowledge towards educational status and other socio-demographic profiles. A total 184 patients were included in this study. In this study, we found 91 subjects (48.9%) knew that heart disease was the most important diabetic complication, if blood glucose level wasn't controlled properly followed by cerebrovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 10 publications
4
21
1
Order By: Relevance
“…Patients' knowledge about diabetic eye disease was also poor in other studies carried out in the South Asian region. Hoque et al in Bangladesh, for example, found that only 4.9% of their study participants were aware about diabetic eye disease [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' knowledge about diabetic eye disease was also poor in other studies carried out in the South Asian region. Hoque et al in Bangladesh, for example, found that only 4.9% of their study participants were aware about diabetic eye disease [9].…”
Section: Discussionmentioning
confidence: 99%
“…An extensive literature search was conducted in formulating the questionnaire and a number of studies based on questionnaires with similar questions were used [8][9][10]. The questionnaire was first drafted by the 3 investigators, 2 family physicians and a community physician.…”
Section: Data Collectionmentioning
confidence: 99%
“…This is slightly higher than 0.5% diabetic patients who had awareness about diabetic foot and peripheral neurological problems in Khulna Diabetic Centre, Bangladesh (Hoque et al). 17 The differences in knowledge regarding foot care among the diabetes patients across the studies could be due to the different levels of diabetes care education provided by the health care professionals in different settings and also on the literacy level of the study subjects.…”
Section: Discussionmentioning
confidence: 99%
“…31 A study conducted in Singapore demonstrated that diabetes related education had changed the self-care practice among diabetic patients. 32 Another study showed that education had a significant role in diabetic awareness to keep correct blood glucose level. 33 It is known that inactivity or a low quantity of physical activity can be a work associated risk factor for diabetes as considering that some professions or occupations, due to its own nature, reduce professionals' physical activity.…”
Section: Discussionmentioning
confidence: 99%